Climate change policy 101 - MacDonald, Donald (My University, 2011)
Similar to other policy issues, climate change policy proceeds in a cyclical fashion that proceeds from agenda setting, to policy development, to implementation, and finally to monitoring and review. Agenda setting involves politicians becoming convinced, usually by the science but also by politics and public opinion, that the climate issue deserves a policy response. Policy development involves a great deal of economic and policy option assessments that are winnowed down to a few options that may have “political traction” (i.e. those politicians think might succeed). Policy implementation involves turning policies into law and regulations that industry and individuals will act upon. Policy review, especially monitoring outcomes, is perhaps the most important phase, and for the climate change issue, the ongoing conclusion to date seems to be that more needs to be done, leading to the policy cycle starting over again. But there are also disturbing signs that this “top-down” approach is no longer working, and more “bottom-up” approaches, linked to the energy sector and clean technology, may become important new forces in forging action on climate change.
Keywords: climate change; policy; environmental policy